Mushroom production for farmers’ additional income - Borah, Tasvina R; Gogoi, Robin; Helim, R (Indian Farming, 2018)
In North-East India with congenial climatic conditions and availability of agricultural, forestry and industrial many different mushroom species can be cultivated commercially. Cultivation of different mushrooms will eye appealing, add variety, flavour and also meet the need for new dishes. Above all the fear of loss of precious life (mushroom phobia) will not persist which usually occurs due to consumption of wild poisonous mushrooms. Many a times reports of mushroom poisoning appeared in the local dailies of Sikkim, Asom and Nagaland. In the north-eastern region the mushroom growers are mostly seasonal or beginners and hence the existing mushroom produce is insufficient to meet the demand. In true sense mushroom industry has not geared up not only in the north-eastern region but also in India due to small mushroom holdings with temporary/seasonal nature. Hence extensive motivation strategies need to be exercised projecting smart mushroom farming as one of the best additional or subsidiary income generating avenue of agriculture.